Metabolite profiling and characterization of Lupinus albus L. and its correlation with antioxidant and alpha-glucosidase inhibitory activities - Khaoula, Hellal (2021)
Diabetes mellitus (DM) is the most widely recognized endocrine disorder in almost all countries. Due to the adverse effects of modern treatment such as hypoglycemic coma, renal complications, stomach upset, and weight gain, the use of medicinal plants as antidiabetic agents has been gaining increasing attention due to their effectiveness. The main objective of this study was to profile and characterize the metabolites presence in the Algerian medicinal food plants that are traditionally used for the treatment of hyperglycemia (Peganum harmala, Zygophyllum album, Anacyclus valentinus, Ammodaucus leucotrichus, Lupinus albus, and Marrubium vulgare). To achieve that aim, this study was carried out in several phases. In the first phase, we aimed to screen the DPPH free radical scavenging, α-glucosidase and nitric oxide inhibitory activities as well as total phenolic content (TPC) of the six Algerian medicinal food plants extracted using different percentage of ethanol (0, 50, 80, and 100%). The findings revealed that the highest TPC of 612.84µg GAE/mg extract was observed in M. vulgare extracted with 80% ethanol. The 100% ethanol extract of A. leucotrichus exhibited the highest free radical scavenging activity with an IC50 value of 26.26 µg/mL. However, the 100% ethanol extract of L. albus seeds was found to be the most potent in in habiting α-glucosidase activity with the lowest IC50 value of 6.45µg/ml. Therefore, it was the best candidate for further investigation in the next phase where the metabolite profiling was conducted using proton nuclear magnetic resonance (1H NMR) spectroscopy. A partial least square analysis (PLS) was used to assess the relationship between that α -glucosidase inhibitory activity of L. albus and the metabolites identified in the extract. Based on the PLS model, isoflavonoids, amino acids, and several fatty acids were identified as metabolites that contributed to the inhibition of α -glucosidase. The PLS model exhibited a perfect goodness of fit where (R2Y (cum) > 0.9) and predictive quality (Q2(cum) > 0.9). For further investigation, the metabolite profile was carried out by using ultra-highperformance liquid chromatography-electrospray ionization-tandem mass spectrometry (UHPLC-ESI-MS/MS) technique in both negative and positive ion mode. A total of 45 metabolites were tentatively identified by means of MS data, together with the interpretation of the observed MS/MS spectra in comparison with those found in the literature. Consequently, in the next part of the study, the 100% ethanolic extract of L. albus seeds was fractionated with different solvent polarity using solid phase extraction (SPE) and the DPPH free radical scavenging, and α-glucosidase inhibitory activities of the resulted fractions were evaluated. This phase provides useful information for the identification of compounds in L. albus seeds fractions by NMR based metabolomics. In total, 35 metabolites were identified from L. albus seeds fractions. Principal component analysis (PCA) is used as a multivariate projection method for visualizing the different composition of four different fractions. Among the fractions studied, the chloroform fraction (CF) exhibits a high free radical scavenging (DPPH) and α-glucosidase inhibitory activities with IC50 values of 4.08 and 20.08 µg/mL, respectively. A PLS model has been successfully performed to correlate the potential active metabolites with the corresponding biological activities. Metabolites such as proline, caprate, asparagine, lupinoisolone C, hydroxyiso-lupalbigenin and some unknown compounds showed high correlation with the bioactivities studied. Autofit of SIMCA treatment exhibited a perfect goodness of fit with R2Y (cum) > 0.9 and a predictive quality of Q2 (cum) > 0.9. Moreover, a total of 25 metabolites were tentatively identified from CF using UHPLC-ESI-MS/MS analysis by comparison with previously reported data. The last phase of this study has been undertaken with the aim to isolate and characterize active metabolites from CF through chromatography techniques. Five compounds including, triolein (2), lupeol (3) β -sitosterol (4), betulinic acid (5), and ursolic acid 13) were isolated from CF. All compounds found to have both α - glucosidase inhibitory and DPPH free radical scavenging activities. Triolein (2) was found to possess the highest α-glucosidase inhibition activity with IC50 value of 3.32 µg/mL , while ursolic acid (13) exhibited the strongest DPPH free radical scavenging inhibitor with IC50 value of 13.97 µg/mL In summary, the findings of this research suggest that L. albus seeds extracts exert antidiabetic activity through their effects as antioxidant and α- glucosidase inhibitors. Triolein, lupeol, β-sitosterol, betulinic acid, and ursolic acid can be contributed to the antidiabetic activity exhibited by L. albus seeds extracts. The outcomes obtained endorse the claims that L. albus seeds extract can be beneficial in the prevention and treatment of diabetes and its associated disorders. To the best of our knowledge, this fingerprint profile is the first extensive study of metabolites from L. albus seeds extract fractions, which may explain the use of L. albus as antidiabetic agent in the Algerian folk medicine and its application in future phytomedicinal preparations for the treatment of diabetes.